Three-dimensional finite element analysis of implant positioning protocols in the maxillary sinus region for zygomatic bone implantation - LI Jing; LI Chenxi; PEI Pei; CHEN Cheng; GONG Zhongcheng (Kouqiang hemian waike zazhi)
[Objective:] To compare the distribution characteristics of biochemical stress on two techniques of zygomatic implant (ZI), sinus slot (SS) and extra sinus (ES), in combination with conventional implants respectively, and to provide theoretical basis for functional restoration of severe atrophic maxilla. [Methods:] Finite element analysis (FEA) models were constituted based on high-resolution computed tomography (CT) scanning data of a patient. ZIs were virtually placed into models with SS or ES techniques combined with two or four conventional implants. The von Mises stress values in implants and the principal stress values in alveolar bone were analyzed. [Results:] The highest von Mises stress was in the configuration of 2 conventional implants and 2 ZIs with ES technique (292 MPa). The lowest von Mises stress level in ZIs was in the configuration of 4 conventional implants and 2 ZIs with the SS technique (184 MPa). The highest maximum principal stress was in the configuration of 2 conventional implants and 2 ZIs with SS technique (31 MPa). The lowest maximum principal stress was in the configuration of 4 conventional implants and 2 ZIs with ES technique (12 MPa). The lowest minimum principal stress was in the configuration of 4 conventional implants and 2 ZIs with the SS technique (|-58| MPa). The highest minimum principal stress value in bone was in the configuration of 2 conventional implants and 2 ZIs with ES technique (|-81| MPa). [Conclusion:] Two ZIs with the SS technique and four conventional implants may be biomechanically safer for the rehabilitation of severe atrophic maxilla.